Remote data acquisition system using ARM9 and GNU/Linux - Alaa Abdalhussain Mashkor (School of Computer and Communication Engineering, University Malaysia Perlis, 2014)
This study aims is to evaluate stress shielding induced by crack interaction using a simple model based on Linear Elastic Fracture Mechanics (LEFM). This simulation based on the determination of the Stress Intensity Factor (SIF) and the changes of stress shielding in different crack interval towards the human phalanx bone.